MENGGUGAT PERSATUAN ROH MANUSIA DENGAN TUHAN: DEKONSTRUKSI TERHADAP PAHAM ITTIHAD DALAM FILSAFAT ABU YAZID AL-BUSTAMI - Dalmeri, Dalmeri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2016)
To Sue the Union of Human Spirit with God: Deconstruction Toward the Concept of Ittihad in the Philosophy of Abu Yazid Al-Bustami. Sufism in Islam has religious and spiritual experience emphasizing more on te spiritual experience of Sufis. This ritual is considered as one way of purification of the spirit or the soul by emptying all atributes that are related to all aspects of earthly life, as well as its relationship with the creatures. This experience emphasizes more on the spiritual nature to juxtapose to God. This spiritual experience could create conflicts and even lead to a mutual misleading. This study seeks to describe the formulation of a union among human spirits based on Abu Yazid’s philosophical thinking. It uses a philosophical approach with the pattern of historical - critical research toward one of the famous sufi’s teachings known as ittihad